Programmatically Dynamic Microcompartmentation in Coacervate‐in‐Pickering Emulsion Protocell. Issue 10 (23rd December 2022) - Chen, Mengqing; Liu, Guoliang; Zhang, Ming; Li, Yanyan; Hong, Xinlin; Yang, Hengquan
Abstract: The desire for exploration of cellular functional mechanisms has substantially increased the rapid development of artificial cells. However, the construction of synthetic cells with high organizational complexity remains challenging due to the lack of facile approaches ensuring dynamic multi‐compartments of cytoplasm and stability of membranes in protocells. Herein, a stable coacervate‐in‐Pickering emulsion protocell model comprising a membraneless coacervate phase formed by poly‐l ‐lysine (PLys) and adenosine triphosphate (ATP) encapsulated in Pickering emulsion is put forward only through simple one‐step emulsification. The dynamic distribution of intracellular components (coacervates in this protocell model) can be manipulated by changes in temperature or pH. This coacervate‐in‐Pickering emulsion protocell system exhibits repeatable cycle stability in response to external stimuli (at least 24 cycles for temperature and 3 cycles for pH). By encapsulating antagonistic enzymes into coacervates, glucose oxidase (GOx) and urease as an example, the control of local enzyme concentration is achieved by introducing glucose and urea to adjust the pH value in Pickering emulsion droplets. This hybrid protocell model with programmatically dynamic microcompartmentation and sufficient stability is expected to be further studied and applied in cellular biology, facilitating the development of lifelike systems with potential in practical applications. Abstract : The coacervate‐in‐Pickering emulsion protocell model fabricated by one‐step emulsifying exhibits high robustness. The coacervate in Pickering emulsion can be dynamically programmed into single‐phase or multi‐compartments with external stimuli (pH and temperature, at least 24 cycles for temperature and 3 cycles for pH), such that the dynamic distribution of intracellular components (enzymes) can be manipulated.